Mosquito Larvicidal Potential of Gossypium hirsutum (Bt cotton) Leaves Extracts against Aedes aegypti and Anopheles stephensi larvae. - Chandrashekhar D Patil; Hemant P Borase; Rahul B Salunkhe; Rahul K Suryawanshi; Chandrakant P Narkhade; Bipinchandra K Salunke; Satish V Patil (Tehran University of Medical Sciences, 2014)
Background: We aimed to extract the ingredients from leaves of Gossypium hirsutum (Bt cotton) using different solvents and evaluate for potential use to control different larval stages of mosquito species, Aedes aegypti and Anopheles stephensi. Methods: Qualitative and quantitative estimation of ingredients from Go. hirsutum (Bt) plant extract was carried out and their inhibitory action against mosquito larvae was determined using mosquito larvicidal assay. Results: LC50  values of water, ethanol, ethyl acetate and hexane extracts for Ae. aegypti were 211.73±21.49,241.64±19.92, 358.07±32.43, 401.03±36.19 and 232.56±26.00, 298.54±21.78, 366.50±30.59, 387.19±31.82 for 4th instar of An. stephensi, respectively. The water extract displayed lowest LC50 value followed by ethanol, ethyl acetate and hexane. Owing to the comparatively better activity of water extract, its efficacy was further evaluated for mos- quito larvicidal activity, which exhibited LC50  values of 133.95±12.79, 167.65±11.34 against 2nd  and 3rd  instars of Ae. aegypti and 145.48±11.76, 188.10±12.92 against 2nd and 3rd instars of An. stephensi, respectively. Crude protein from the water extract was precipitated using acetone and tested against 2nd, 3rd and 4th instars of Ae. aegypti and An. stephensi. It revealed further decrease in LC50 values as 105.72±25.84, 138.23±23.18, 126.19±25.65, 134.04±04 and 137.88±17.59, 154.25±16.98 for 2nd, 3rd and 4th instars of Ae. aegypti and An. stephensi, respectively. Conclusion: Leaves extracts of Go. hirsutum (Bt) is potential mosquito larvicide and can be used as a potent alter- native to chemical insecticides in integrated pest management.